Manajemen Pengembangan Dosen sebagai Upaya Meningkatkan Mutu Sekolah Tinggi Pariwisata Ampta Yogyakarta - Siti Rokhmi Lestari (Media Wisata, 2014)
The aim of this study is to describe the planning and development of lecturers human resources in AMPTA Tourism School as well as to know the professionalism of lecturers and quality assurance in the AMPTA Tourism School of Yogyakarta. From this study, it can be concluded that, in general, the human resource planning and development of lecturers, as well as quality assurance in AMPTA Tourism School, have not been fully implemented in accordance with the existing regulations and legislation.However, AMPTA Tourism School is on the right track in terms of lecturers professionalism development and networking establishment with external stakeholders. Implementation of human resources development is carried out through formal and informal ways.